Corrosion of engineering ceramic materials by molten iron part I: Silicon nitride and SiAlON. (June 2016) - Hnatko, M.; Tatarková, M.; Galusková, D.; Bystrický, R.; Lenčéš, Z.; Sedláček, J.; Šajgalík, P.
Highlights: The corrosion resistance of successfully sintered Si3 N4 and SiAlON dense ceramic materials by molten iron at 1600 °C in N2 atmosphere has been investigated. Si3 N4 reacts with molten Fe very rapidly. Main corrosion products of Si3 N4 were the iron silicides. SiAlON ceramic exhibited the higher corrosion resistance compared to the Si3 N4 due to the formation of protective layer of Al2 O3 in the initial stages of the corrosion process. The strength of the corrosion of SiAlON in the molten Fe significantly decreases up to 20% of the initial strength. Abstract: The corrosion resistance of two different polycrystalline materials (Si3 N4, SiAlON) by molten iron at 1600 °C has been investigated. Silicon nitride reacts with molten iron very rapidly while SiAlON exhibited the improved corrosion resistance. Better corrosion resistance of SiAlON is caused by the formation of protective layer of Al2 O3 in the initial stage of corrosion test. In the present work the influence of exposure time on the residual strength of the polycrystalline materials has also been estimated. The strength of the SiAlON after 8 h of corrosion was only 20% of the initial strength of the same material before corrosion.